A compulsão alimentar entre sintoma e sinthoma - Santos, Magna Maria de Oliveira (2022)
This research is a theoretical essay based on psychoanalysis with a focus on the latest Lacanian concepts inherited from Freudian concepts. This research is guided by the symptom of eating compulsion in its forms of presentation, neurosis or psychosis, which can acquire its stability in the confluence between life and death drives. Whose entanglements of symptom and sinthome will make their mark and hystoire. The intention is to demonstrate that in the paths of an analysis, the symptom of binge eating can serve to structure a certain speakingbeing (parlêtre) during the analytical journey. It is necessary to consider that the body that manifests a compulsion, as a speaking-being (parlêtre), plays between life and death, between the pleasure of eating and the pain of guilt, going through a hellish war. The eating compulsion has repetitive and transferential fragments, as an act that commands the subject, directing him to the repetition and submission of his act, since in it and through it, he is alienated to the jouissance of the Other, agreeing symptomatically. However, when his jouissance is equipped with the tingling that makes him speak, he encounters another jouissance, that is, another satisfaction in a symptomatic concordance. Understanding the eating compulsion as possessing a singular function for the subject is to think about the destinies of desire and drives in the current clinic, and extract the subjectivities from it